DETERMINAN KEPUASAN KERJA PEGAWAI SMP DAN SMA DELI MURNI BANDAR BARU - FERY NANDO PERANGIN-ANGIN (LP2MTBM MAKARIOZ, 2019)
This study was to determine compensation, promotion, work environment, and job satisfaction in Deli Murni Bandar Baru Junior and Senior High Schools and the influence of Leadership, competence and compensation on employee job satisfaction, both simultaneously and partially. The method used is descriptive and verification methods, then the research method used is descriptive survey method and explanatory survey method. The type of investigation in this study is causality. The unit of analysis in this study is individuals, namely all employees in SMP and SMA Deli Murni Bandar Baru, amounting to 58 people using the census method. The time horizon in this study is cross-sectional. The analytical tool used is SPSS. The data analysis design used in this study is the path analysis approach, with the test design carried out in the study is the correlation test and the test of determination. The results of this study are Leadership and Competence, and job satisfaction in Deli Murni Bandar Baru Middle and Senior High Schools is good, and employee evaluation of compensation is sufficient. but still needs improvement and improvement. Leadership, competence and compensation simultaneously affect job satisfaction. Leadership partially influences job satisfaction. Competency partially has a positive effect on job satisfaction. Partial compensation has a positive effect on job satisfaction. Compensation provides the greatest influence on job satisfaction.